The largest blindsnake in Mesoamerica: a new species of Typhlops (Squamata: Typhlopidae) from an isolated karstic mountain in Honduras - Townsend, Josiah H.; Wilson, Larry David; Ketzler, Lorraine P.; Luque-Montes, Ileana R. (Zootaxa, 2008)
A distinctive new species of Typhlops is described from Parque Nacional Montaña de Santa Bárbara, 1550 m elevation, Departamento de Santa Bárbara, Honduras. The holotype and only known specimen of this new taxon is the largest specimen of the genus thus far reported from Mexico and Central America, and is further differentiated from all other Mesoamerican Typhlops by having 22–22–22 scales around the body and by having a dark brownish gray dorsum with a well-defined pale yellowish gray to immaculate white ventral coloration. This species is a member of the Caribbean Arc Group of Typhlops. An updated key to the Typhlopidae of Mesoamerica is provided.